Kualitas Sludge Hasil Ikutan Proses Pembuatan Biogas dari Feses Sapi Perah dengan Berbagai Kadar Air - Marlina, Eulis Tanti; Hidayati, Yuli Astuti; Benito AK, Tubagus (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
This research aims to study the  influence of water content in the production of biogas from dairy cattle  feces to the quality of sludge. The method used  in  this study  is the experimental method using a completely  randomized design, with  three  treatments  (P1 =  substrate water  content  of dairy  cow  feces 40%, P2 = substrate water content of dairy cow  feces 60%, P3 = substrate water content of dairy cow feces  80%  ) with  six  replications. Variables measured were  levels  of N  total, P2O5, K2O. The  results showed that 1) the treatment did not significantly affect total N concentration, but significantly different levels of P2O5 and K2O, 2) substrate water content 60% (P1) and 80% (P2) generate levels of P2O5 and K2O are highest, ie 1.03% and 1.13% (P2) and 0.84% and 1.00% (P3).